PENGARUH GOOD CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN, LIKUIDITAS, LEVERAGE, KEBIJAKAN DIVIDEN, DENGAN NILAI PERUSAHAAN - LILIAN MARCELINE; ANWAR HARSONO (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research was to analyze the effect of good corporate governance (independent commissioner, managerial ownership, audit committee), company’s characteristics (firm size and return on equity), liquidity, leverage, dividend policy, with firm value. Sample of this research are 55 non financial companies listed in Indonesia Stock Exchange during the research period 2013 until 2015, thus totaled 165 data. Sample selection method used was purposive sampling. The hypothesis was tested using multiple regression method. In this research, firm value were measured by Tobin’s Q.The empirical evidence of this research indicated that audit committee and leverage has negatively effects firm’s value. Return on equity has positively effects firm’s value. On the other hand, independent commissioner, managerial ownership, firm size, liquidity, dividend policy have no influence on firm value.